2015
DOI: 10.6018/analesps.31.1.162281
|View full text |Cite
|
Sign up to set email alerts
|

Differential effectiveness of two anxiety induction procedures in youth and older adult populations. [Eficacia diferencial de dos procedimientos de inducción de la ansiedad en poblaciones de jóvenes y adultos]

Abstract: Título: Eficacia diferencial de dos procedimientos de inducción de la ansiedad en poblaciones de jóvenes y adultos. Resumen: En este estudio se comparó la eficacia en personas mayores y jóvenes de dos procedimientos habituales para inducir experimentalmente ansiedad: a) frases auto-referenciales Velten combinadas con música; b) escenas de películas. Así, este trabajo extendió hallazgos previos en este campo a la poca estudiada área de la inducción de estados de ánimo en la edad avanzada. Se asignó aleatoriamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To investigate the relationship between aesthetic appreciation and anxiety, we designed study 2, consisting of a behavioural (study 2a) and a psychophysiological (study 2b) protocols. In these studies, we employed atonal and micropolyphonic musical pieces that were demonstrated to induce either anxiety [84,85,87,[101][102][103][104] or aesthetic appreciation [105].…”
Section: (B) Studymentioning
confidence: 99%
“…To investigate the relationship between aesthetic appreciation and anxiety, we designed study 2, consisting of a behavioural (study 2a) and a psychophysiological (study 2b) protocols. In these studies, we employed atonal and micropolyphonic musical pieces that were demonstrated to induce either anxiety [84,85,87,[101][102][103][104] or aesthetic appreciation [105].…”
Section: (B) Studymentioning
confidence: 99%